(untitled) (Research, Society and Development, 2022)
Tree morphometric studies seek to convey an idea of interdimensional relationships, reconstitute the space occupied by trees, judge the degree of population competition, as well as inferences about stability, vitality and productivity of each individual. In this context, it is deemed necessary to promote studies in agroforestry systems that aim at the integration between tree species, forage species and animals in order to obtain products or services from these components. In this work, 200 individuals were evaluated, divided between 4 forest species of great relevance in the market, implanted in a silvopastoral system in the municipality of Belterra, Pará. The cumaru (Dypteryx sp) was planted in double rows (10 x10 m), the African mahogany (Khaya sp) in double (10x10 m) and single rows (10 meters between plants), teak (Tectona grandis) in triple rows (7x7 m) and andiroba (Carapa guianensis) arranged in five-fold rows of 7x7 m. Among the parameters evaluated, the average annual increment was calculated, both for height and diameter. Mahogany presented superior results for Total Height, at 14.8% for andiroba, 38.4% in relation to teak and 21.2% for cumaru. There was a difference between the values of canopy insertion and commercial height, which varied, for all species studied, from 3.8 to 55.2 %, which justifies the collection of these variables separately. Mahogany was the species that presented the best results in terms of population and morphometrics. There was a tendency for individuals from lower strata to promote development in a more accentuated crown diameter when compared to the other variables.